Histological Features of the Gastrointestinal Tract of Wild Indonesian Shortfin Eel, Anguilla bicolor bicolor (McClelland, 1844), Captured in Peninsular Malaysia. (22nd December 2014) - Nasruddin, Nurrul Shaqinah; Azmai, Mohammad Noor Amal; Ismail, Ahmad; Saad, Mohd Zamri; Daud, Hassan Mohd; Zulkifli, Syaizwan Zahmir
Abstract : This study was conducted to record the histological features of the gastrointestinal tract of wild Indonesian shortfin eel, Anguilla bicolor bicolor (McClelland, 1844), captured in Peninsular Malaysia. The gastrointestinal tract was segmented into the oesophagus, stomach, and intestine. Then, the oesophagus was divided into five (first to fifth), the stomach into two (cardiac and pyloric), and the intestine into four segments (anterior, intermediate, posterior, and rectum) for histological examinations. The stomach had significantly taller villi and thicker inner circular muscles compared to the intestine and oesophagus. The lamina propria was thickest in stomach, significantly when compared with oesophagus, but not with the intestine. However, the intestine showed significantly thicker outer longitudinal muscle while gastric glands were observed only in the stomach. The histological features were closely associated with the functions of the different segments of the gastrointestinal tract. In conclusion, the histological features of the gastrointestinal tract of A. b. bicolor are consistent with the feeding habit of a carnivorous fish.